40th Annual David W Smith Workshop on Malformations and Morphogenesis: Abstracts of the 2019 Annual Meeting. Issue 4 (10th March 2020) - Braddock, Stephen R.; Lipinski, Robert J.; Carey, John C.
Abstract: The 40th Annual David W. Smith Workshop on Malformations and Morphogenesis occurred August 23rd ‐28th, 2019 at the Snowbird Resort in Snowbird, Utah. The Workshop, which honors the legacy of David W. Smith, brought together clinicians and researchers interested in congenital malformations and their underlying mechanisms of morphogenesis from around the world. In addition to mechanisms of morphogenesis and delineation of new syndromes, the Workshop highlighted five themes: deformations, disruptions and fetal dysmorphology; orofacial clefting; central nervous system malformations; ciliopathies; and X‐linked intellectual disabilities. This Conference Report includes the abstracts presented at the 2019 Workshop.